Ruta graveolens, Pelargonium graveolens AND Hibiscus cannabinus AS NATURAL INHIBITORS OF GROWTH OF Candida albicans - Reis, Camila Mara dos (2021)
Candidiasis is an infection caused by fungi of the genus Candida, Candida albicans being the species that most causes the disease in Brazil. The Fluconazole is the conventional medicine used as a treatment of these infections; however, it causes many adverse reactions in the patient and its continued use can induce the resistance of the pathogen. The medicinal plants can be very effective as an alternative treatment of diseases and have been used in folk medicine for years. In this study, it was evaluated the antifungal activity of extracts of Ruta graveolens, Pelargonium graveolens and Hibiscus cannabinus against the fungal development of Candida albicans, comparing the efficiency of these extracts to Fluconazole. The extracts were prepared in the concentration of 1g of the plant for each 5 mL of alcohol 70%. The data were obtained using the agar diffusion method. The minimum inhibitory concentration test (MIC) was performed, and showed that R. graveolens was able of inhibiting 100% of the pathogen when using 100 mg.ml-1 concentration. From the results obtained, it was possible to conclude that R. graveolens was the most effective extract when compared to Fluconazole, suggesting that this extract can be used as an alternative to conventional treatment to improve the efficiency of current treatments. The extracts of P. graveolens and H. cannabinus also presented antifungal activity but in smaller proportion than Fluconazole.